SUBSTÂNCIAS HÚMICAS DO SOLO EM SISTEMAS AGRÍCOLAS MANEJADOS NO ECÓTONO CERRADO-PANTANAL - Vitor Fabian Salvador , João; Sérgio Rosset , Jean; da Silva Menezes , Roniedison; Panachuki , Elói; Maria Cutier Dominguez Pereira , Cecília; Clara da Costa Rodrigues , Ana (ANAIS DO ENIC, 2026)
-